Efficacy and safety of phosphodiesterase type-5 inhibitors for pulmonary arterial hypertension: A meta-analysis focusing on 6MWD. (June 2015) - He, Chao-Jie; Chen, Shao-Jie; Wang, Jie; Zhu, Chun-Yan; Yin, Yue-Hui
Abstract: Background and objective: Phosphodiesterase type-5 inhibitors (PDE-5 inhibitors) have been suggested as a first-line drug for treating pulmonary arterial hypertension (PAH). The aim of present meta-analysis was to fully evaluate the efficacy and safety of treating PAH with PDE-5 inhibitors, focusing on the improvement of 6-min walk distance (6MWD). Methods: Studies were identified from The Cochrane Library, EMBASE, and PUBMED databases. We calculated odds ratios (OR) for dichotomous data and weighted mean differences with 95% confidence intervals (CI) for continuous data. Results: Six studies with a total of 1056 patients (729 patients in PDE-5 inhibitors treatment group and 327 patients in placebo group) were included. All-cause mortality rate in the control group and PDE-5 inhibitors group was 2.6% and 0.7%, respectively. In an average of 12.3-week follow-up, PDE-5 inhibitors treatment was associated with a 71% reduction in mortality (OR 0.29; 95 %CI 0.07–1.15; P = 0.08), and increased 6MWD by 40.17 m, improved NYHA functional class and hemodynamic parameters. As for monotherapy and combination therapy patients, 6MWD has improved by 48.94 m and 21.75 m, respectively. Conclusions: The results of present meta-analysis suggest that treatment with PDE-5 inhibitors improves the 6MWD, clinical symptoms, hemodynamic parameters, and a tendency of survival benefits. In patients treated with PDE-5 inhibitor monotherapy, the 6MWD significantly increased when compared to combination therapies.